2019
DOI: 10.3390/ijms20071767
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Activity of TRPA1 and TRPV1 in the Intervertebral Disc: Association with Inflammation and Matrix Remodeling

Abstract: Transient receptor potential (TRP) channels have emerged as potential sensors and transducers of inflammatory pain. The aims of this study were to investigate (1) the expression of TRP channels in intervertebral disc (IVD) cells in normal and inflammatory conditions and (2) the function of Transient receptor potential ankyrin 1 (TRPA1) and Transient receptor potential vanilloid 1 (TRPV1) in IVD inflammation and matrix homeostasis. RT-qPCR was used to analyze human fetal, healthy, and degenerated IVD tissues fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 61 publications
1
35
0
Order By: Relevance
“…Moreover, cartilage-specific TRPV4 knockout in mice reduced age-related osteoarthritis [22]. The exploration of TRP channels in the IVD is at its infancy, with only few published studies [23][24][25][26][27]. Most of the known TRP channel genes are expressed in the IVD [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, cartilage-specific TRPV4 knockout in mice reduced age-related osteoarthritis [22]. The exploration of TRP channels in the IVD is at its infancy, with only few published studies [23][24][25][26][27]. Most of the known TRP channel genes are expressed in the IVD [26].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, TRPV4 has been associated with reduced osmolarity and pro-inflammatory cytokines in bovine nucleus pulposus cells [23]. Additionally, treatment with IL1β increases TRPV4 gene expression in human IVD cells, thus revealing a potential inflammatory role of the channel in IVDs [27]. Nevertheless, the roles of TRPV4 in mechanosensing and mechanotransduction in the IVD remain to be established.…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in the AF cell density, as frequently observed in degenerated IVDs, alters the balance of anabolism:catabolism ratio in the extracellular matrix (ECM), changing the AF mechanical, biological, and structural properties [ 69 , 70 , 71 ]. Therefore, regenerative strategies aim to repopulate a degenerated IVD with healthy cells (cell therapy) or stimulating the existing cells to regulate the ECM reaching an enhanced composition, quantity, and structure (biomolecule and gene therapy) [ 81 , 82 , 83 , 84 , 85 ]. ECM remodeling is crucial to control the action of biochemical mediators such as cytokines (interleukins), growth factors, and enzymes (metalloproteinases and heparanase) to ultimately stop or reverse the IVD degeneration process [ 86 , 87 , 88 , 89 ].…”
Section: Regenerative Strategiesmentioning
confidence: 99%
“…To understand the players involved in peripheral pain hypersensitivity, the altered expression of selected membrane receptors was investigated in specimens from patients of different ages and genders, with confirmed diagnosis of CLBP. TRPV1-4, TRPA1, and TRPM8 were selected because of their expression in peripheral sensory neurons as molecular nociceptors, actively transducing thermal, chemical, and mechanical stimuli [13,24], thus being involved in CLBP. For example, TRPV4 acts as a sensor of mechanical or osmotic signals and it is present not only in the nervous system but also in several musculoskeletal tissues, including cartilage, bone, and synovium.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Also, TRPV1 is known to be stimulated by several inflammatory neuropeptides and signaling molecules [14] and overexpressed in osteoarthritis [38,39]; thus, it is reasonable to expect a similar pattern of expression in specimens retrieved from patients affected by CLBP. Moreover, in inflammatory tissue, it is often co-expressed with TRPA1 [5] that can be equally stimulated by an array of molecules present in inflammation and in acute mechanical hypersensitivity [2,13,41]. Finally, many papers reported that also TRPM8 is expressed on both Aδ and C fiber and overexpressed in pain conditions, where it plays a role in amplifying pain sensation after injury, particularly in models of neuropathic pain.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%